2010
DOI: 10.1055/s-0030-1255445
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of a Recombinant von Willebrand Factor Drug Candidate

Abstract: The complex structure, large size, and multiple posttranslational modifications of von Willebrand factor (VWF) presented a technological challenge for the production of recombinant VWF (rVWF). Nonetheless, we developed an rVWF product for treating von Willebrand disease, whereupon rVWF is coexpressed with recombinant factor VIII (rFVIII) in Chinese hamster ovary cells used to produce rFVIII for the treatment of hemophilia A. Here we describe the characterization of the structure and function of the rVWF drug p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 34 publications
4
44
0
Order By: Relevance
“…The higher specific activity of rVWF than in pdVWF-pdFVIII complex products has been described previously. 25 The VWF:CB results in our study are also consistent with previous findings which showed that the specific collagen-binding activity of the rVWF-rFVIII study product (defined as the ratio VWF:CB/VWF:Ag) is higher (1.14 6 0.16) when compared with pdVWF-pdFVIII (0.84) or pdVWF (0.81 6 0.06). 25 Higher ratios of VWF:RCo/VWF:Ag correspond to a higher relative amount of ultra-large molecular weight (ULMW).…”
Section: Discussionsupporting
confidence: 92%
“…The higher specific activity of rVWF than in pdVWF-pdFVIII complex products has been described previously. 25 The VWF:CB results in our study are also consistent with previous findings which showed that the specific collagen-binding activity of the rVWF-rFVIII study product (defined as the ratio VWF:CB/VWF:Ag) is higher (1.14 6 0.16) when compared with pdVWF-pdFVIII (0.84) or pdVWF (0.81 6 0.06). 25 Higher ratios of VWF:RCo/VWF:Ag correspond to a higher relative amount of ultra-large molecular weight (ULMW).…”
Section: Discussionsupporting
confidence: 92%
“…21 A human recombinant VWF (rVWF), vonicog alfa, which is synthesized by a genetically engineered CHO cell line coexpressing the VWF and the FVIII genes, has been developed to advance the standard of care for patients with VWD and make the treatment independent from plasma supply. 22 Vonicog alfa is the first rVWF manufactured in the absence of animal or other human plasma proteins, rendering theoretical the risk of transmission of adventitious agents and other blood-borne pathogens such as prions. In contrast to plasma-derived coagulation factors, no therapeutic protein produced by a recombinant cell line has ever resulted in virus transmission, which is primarily due to the ability to control the recombinant cell line manufacturing environment.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] In contrast to VWF concentrates derived from plasma, rVWF has no exposure to the human protease ADAMTS13 during the production process and therefore contains intact HMWM and ULM. 22 The presence of ULM and the higher purity also contribute to a greater specific activity of rVWF measured as VWF:ristocetin cofactor activity (VWF:RCo) relative to VWF:antigen (VWF:Ag).…”
Section: Introductionmentioning
confidence: 99%
“…20,21 VWF ristocetin cofactor activity (VWF:RCo) was determined using a turbidimetric analyzer (BCS system; Siemens). ADAMTS13 activity (ADAMTS13:Ac) was analyzed using the synthetic fluorogenic fluorescence resonance energy transfer substrate units (FRETS-U)/VWF73 minimal peptide substrate (Peptanova), essentially as described.…”
Section: Methods Rhvwf and Recombinant Human Adamts13mentioning
confidence: 99%
“…20 It thereby resembles VWF that is newly released into plasma from Weibel-Palade bodies of endothelial cells and platelet ␣-granules. 25 Although in healthy persons the UL portion of the newly released VWF is rapidly processed to smaller multimers by ADAMTS13, it persists for a much longer time in TTP patients who have a severe ADAMTS13 deficiency.…”
Section: Pathophysiologic Relevance Of Rvwf As a Trigger Of Ttpmentioning
confidence: 99%